Effects of Sheep Manure Application on the Production of Dwarf Napier Grass (Pennisetum Purpureum Cv. Mott) - Jusoh, Shokri (2005)
Studies were conducted to evaluate the utilization of sheep manure as fertilizer for growing Dwarf Napier grass(Pennisetum purpureum cv. Mott). The grass received one of six maintenance N fertilizer treatments namely: 1) control, 2) 200 kg N ha-1 from urea, 3) 200 kg N ha-1 from sheep manure, 4) 100 kg N ha-1 from sheep manure, 5) 50-50 mixture of sheep manure and urea at the rate of 200 kg N ha-1 and 6) a 50-50 mixture of sheep manure and urea of 100 kg N ha-1.Urea was applied in 4 split applications per year while sheep manure was applied once over a 12 month period.The effect of types of fertilizer used on the growth performance and nutritional quality of the grass were evaluated in study 1.The organic fertilizer as either sheep manure alone or as combination with urea gave better growth performance of the grass in terms of tiller height, tiller number and leaf area index over 6 cycles of 6 weeks per cycle. The treatment with 200 kg N ha-1 of sheep manure gave highest dry matter yield (16 t ha-1 yr-1) compared to control (10 t ha-1 yr-1). The leaf: stem ratio of the grass shows that the leaf fraction increased significantly over time. The urea fertilizer gave higher crude protein(13%) compared to 12% in other treatments.Grass fertilized with mixed fertilizer gave higher NDF (73.21%),ADF (40%) and sheep manure gave higher ash concentration (>10%) and low ADL concentration (<0.25%).Study 2 was conducted to assess the effects of different fertilization regime on the soil chemical properties. The soil fertilized with sheep manure and urea were not significantly difference over a 12-month period. The sheep manure also sustained the plant nutrient in the soil, which was indicated by stabilised soil organic matter and cation exchange capacity over six month. The overall availability of macronutrients in the soil was increased in the soil fertilized with sheep manure compared to control and urea treatments.The influence of the types of fertilizer used on the ensiled product of the grass was determined in Study 3.The urea fertilized silage gave highest concentration of acetic acid (87.5 mm/L) while the silage with sheep manure as fertilizer gave higher concentration butyric acid (110.3 mm/L) and it contributed to the aerobic stability of the silage. When these plants were later used in animal feeding trial, the intake of silage by lambs was higher for grass silage fertilized with urea and control (800 g day-1) than other treatments. However, the grass silage under organic fertilizer, either as sheep manure only or a mixture of sheep manure provided better digestibility (>60%).The average daily gain of the lambs fed grass silage show that the fertilized grass, i.e.: sheep manure and urea (130 g day-1) was higher compared to control (<50 g day-1).The treatments with sheep manure and mixed fertilizer did not show any differences in terms of animal performance.In conclusion, the organic fertilizer, either as sheep manure alone or in combination with urea can be used to fertilize pasture grass because it was found relatively better as compared to urea fertilizer alone.This is because it gave a good balance between yield and nutritive quality